Factors affecting the student evaluation of teaching scores: evidence from panel data estimation - Andrade, Eduardo de Carvalho; Rocha, Bruno de Paula (Estudos Econômicos (São Paulo), 2012)
We use a random-effects model to find the factors that affect the student evaluation of teaching (SET) scores. Dataset covers 6 semesters, 496 undergraduate courses related to 101 instructors and 89 disciplines. Our empirical findings are: (i) the class size affects negatively the SET score; (ii) instructors with more experience are better evaluated, but these gains reduce over time; (iii) participating in training programs, designed to improve the quality of teaching, did not increase the SET scores; (iv) instructors seem to be able to marginally 'buy' a better evaluation by inflating students' grade. Finally, there are significant changes in the rankings when we adjust the SET score to eliminate the effects of variables beyond instructors' control. Despite these changes, they are not statistically significant.